Decisions about the Beauty of Lithuania in Jean Mauclère’s ’Sous le ciel pâle de Lithuanie’ - Dručkutė, Genovaitė (Literatūra, 2020)
Drawing on the theoretical premises of imagology and geocriticism, the article analyzes the aesthetic experience of the traveler who traverses Lithuanian cities (Vilnius, Kaunas, Klaipėda), walks across small towns, stops over in villages, and makes his way to the seaside. The local aesthetic identity of the newly discovered country, i.e. its beauty and/or loathsomeness, is revealed by the author Jean Mauclère through a few perspectives: on the one hand, it is the beauty of nature, folk and professional art (architectural exteriors and interiors, fine arts, music), the physical type of Lithuanian men and women. This identity, as Mauclère suggests, reveals itself in the contexts of local history, traditions and culture. Although the author seeks to remain objective in his description of his new aesthetic experience in Lithuania, he remains a representative of his own French culture and its traditions nonetheless. On the other hand, he underlines the otherness of the novelty of his experience.